Salvage Therapy With Low-Dose Ruxolitinib Leads to a Significant Improvement in Bronchiolitis Obliterans Syndrome in Patients With cGVHD After Allogeneic Hematopoietic Stem Cell Transplantation - Zhao, Yanmin (Front Pharmacol, 2021)
Bronchiolitis obliterans syndrome (BOS) is a life-threatening pulmonary manifestation of chronic graft versus host disease (cGVHD) post-allogeneic hematopoietic stem cell transplantation (HSCT), without clear standard of care. This study included 30 patients undergoing an allogeneic HSCT for a hematological malignancy and the outcomes with post-HSCT BOS treated with ruxolitinib as a salvage treatment were reviewed. After a median duration of ruxolitinib therapy of 9.25 (1.5–27) months, the best overall response (BOR) rate was 66.7%: three patients (10.0%) achieved complete remission, and 17 (56.7%) achieved partial remission. The median time from initiation of ruxolitinib to achieve the best responses was 3 months. Since initiating ruxolitinib, forced expiratory volume in 1 s of predicted (FEV1%pred) slightly increased after 3 and 6 months compared with measurements before ruxolitinib in responders. Only FEV1%pred mild decline before ruxolitinib with a ratio ≤15% was an independent predictor to achieve a response to ruxolitinib. Eleven patients (36.7%) had severe pulmonary infection of ≥3 grade. Following a median follow-up of 318 days after ruxolitinib, the 2-years incidence of nonrelapse mortality and 2-years overall survival rate after ruxolitinib among patients with BOS was 25.1 and 62.6%, respectively. Ruxolitinib is a promising treatment option to improve the prognosis of post-HSCT BOS.